Acute & Sub Acute Toxicity Studies of Hydroalcoholic Extract of Solanum Xanthocarpum Whole Plant - Singh, Renu; Tiwari, Yogesh; Koshti, Deepak (Journal of Biomedical and Pharmaceutical Research, 2022)
The present study is designed to evaluate the safety of aqueous: methanolic (40:60) extract of Solanum xanthocarpum whole plant (SXWP) by determining its potential toxicity after acute and subacute administration in male wistar albino rats. Medicinal plants might deliver a few organic activities in people, but generally very little is known about their toxicity. Though, safety should be the overriding criterion in the selection of medicinal plants for use in healthcare systems, several drugs produce acute and obvious signs of toxicity which are used in the traditional system of medicine. The purpose of toxicity testing is to provide adequate database to make decision concerning the toxicology properties of chemicals and commercial products and to decide whether a drug or chemicals will be safe or not. Results concluded that SXWP extract produce beneficial effect on some blood parameters upon oral administration. Biochemical parameter such as total protein content was changed which may not be beneficial but lowering of lipid profile can be beneficial for long term use. There were no significant change in the other serum parameters may proved its long term use, the kidney parameters too remain unchanged. Further studies are needed to verify the effect of low, medium and high dose for chronic administration of SXWP extract. Keywords: Methanolic, Extract, Solanum xanthocarpum, Toxicity, Chronic, Acute